Characterization of IS1272, an insertion sequence-like element from Staphylococcus haemolyticus. - Archer, G L (1996)
We have previously shown (G. L. Archer, D. M. Niemeyer, J. A. Thanassi, and M. J. Pucci, Antimicrob. Agents Chemother. 38:447-454, 1994) that some methicillin-resistant staphylococcal isolates contain a partial deletion of the genes (mecR1 and mecI) that regulate the transcription of the methicillin resistance structural gene (mecA). When a fragment of DNA inserted at the point of the mecR1 deletion was used as a probe, hybridization with multiple bands was detected for Staphylococcus haemolyticus genomic DNA. In the present study, DNA sequencing of four unique clones recovered from a lambda library of S. haemolyticus revealed identical 1,934-bp elements. Each element, designated IS1272, contained 16-bp terminal inverted repeats (sequence identity, 15 of 16 bp) and two open reading frames of 819 and 687 bp; there were no flanking target site duplications. Database searches yielded amino acid homology with proteins predicted to be encoded by open reading frames from a putative insertion sequence element from Enterococcus hirae. DNA probes from each end and the middle of IS1272 were hybridized with restriction endonuclease-digested genomic DNA from clinical S. haemolyticus, Staphylococcus epidermidis, and Staphylococcus aureus isolates. Each of the 20 or more copies of the element found in S. haemolyticus isolates was intact, and copies were found in most chromosomal SmaI fragments. S. aureus and S. epidermidis isolates contained mostly incomplete fragments of the element, and there were many more hybridizing fragments in methicillin-resistant than in methicillin-susceptible isolates. IS1272, which appears to be primarily resident in S. haemolyticus, has disseminated to multiple staphylococcal species and is prevalent in multiresistant isolates.